Does Religious Education as an examination subject work to promote community cohesion?: An empirical enquiry among 14- to 15-year-old adolescents in England and Wales - Francis, Leslie J. (British journal of religious education, 2017)
This study begins by examining the way in which, in both England and Wales, Religious Education has become implicated in political discussion regarding the role of education in promoting community cohesion. The relationship between taking Religious Education as an examination subject and attitude towards religious diversity (as an affective indicator of community cohesion) is then explored among 3052 14- to 15-year-old students. After controlling for contextual factors (school type and geographical location), personal factors (sex and age), psychological factors (psychoticism, neuroticism and extraversion) and religious factors (Christian affiliation, worship attendance, personal prayer and belief in God), a small but significant positive association was found between taking Religious Education as an examination subject and attitude towards religious diversity. This finding may be interpreted as supporting the view that Religious Education works to promote community cohesion, although the wider debate that the community cohesion agenda has generated among religious educators needs further exploration.